Effect of Long-term Use of Fertilizers and Organics on Phosphorus Dynamics in Rainfed Maize-Wheat Cropping System - and S.S. Paliyal, Upinder Sharma (Journal of the Indian Society of Soil Science, 2014)
A study on phosphorus (P) dynamics under long-term use of variable doses of fertilizers and organics in rainfed maize-wheat system was carried out on Typic Ustipsamments of low hill zone of Himachal Pradesh between rabi (2007-08) and kharif (2008) seasons in the ongoing long-term fertilizer experiment at the research farm of CSK HPKV, HAREC, Dhaulakuan. Surface soil (0-0.15 m) after sixteen cropping cycles was analyzed for different forms of P and subjected to P adsorption studies. Water extractable P and bicarbonate extractable organic P decreased, whereas bicarbonate extractable inorganic P, sodium hydroxide extractable inorganic P, hydrochloride extractable P and residual P content registered an increase over the initial content in all the treatments. Treatments receiving P fertilizer showed greater increase than those without it. The decrease was maximum in case of 100% N and minimum in 100% NP + FYM (farmyard manure). The sodium hydroxide extractable organic P was, in general, stable with continuous cropping and fertilization. Use of N alone led to decline in all forms of P, while addition of P increased NaHCO3-Pi, NaOH-Pi, NaOH-Po, HCl-P, residual-P and total P. Addition of 100% N alone resulted in maximum P adsorption, and soils with only FYM treatment resulted in lowest P adsorption.